An Exploratory Study on the Income of Bentor Drivers : A Comparison Between Maxim-affiliated and Conventional Transport Services - Mirta Mirta; Melizubaida Mahmud; Yulianti Toralawe; Agil Bahsoan; Ardiansyah Ardiansyah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the differences in income levels between online (Maxim) and conventional motorcycle taxi drivers, and to identify the factors influencing the economy of online (Maxim) and conventional transport drivers. The research employs a qualitative method with a descriptive approach.The findings reveal a noticeable difference, where the average income of online motorcycle taxi drivers is higher than that of conventional drivers in Gorontalo City. Then, several factors influence the economy of those drivers, particularly the conventional drivers that switch to online transportation, including the utilization of technology and application access, flexible working hours, operating cost, tariff, total number of passengers, service quality, and distance.